Competitiveness, adjustment and macroeconomic risk management in the eurozone - Peter Spahn (Research On Money in the Economy (ROME), 2013)
Gaps in competitiveness, rooted in economic as well as in political factors, characterise postwar European economic history. The eurozone experience showed the emergence of large current account imbalances. The peculiar mixture of financial markets integration and national cycles in wages and prices gave rise to severe macroeconomic instability. The Swan Diagram is used to analyse alternative adjustment policies. Although there are signs of convergence in wage costs, the overall picture of EMU remains somewhat gloomy, requiring the decision between full political union or a renewed gold standard.
Keywords: 330; Currency union; euro crisis; current account imbalances; wage policy; Swan diagram